MENGUNGKAP PEMIKIRAN MASLAHAT SEBAGAI DALIL HUKUM ISLAM - Tarmizi, Tarmizi (STAIN Jurai Siwo Metro, 2010)
AbstractThis study discusses the concept of maslahat as the law theorem of Islam. Recently, maslahat as a study is being discussed. The facts indicates that maslahat is increasing rapidly in line with the humanâs needs. The change of the societyâs condition and situation from time to time brings about complexity of humanâs problems. This influences and changes the humanâs need structure and their maslahat which in turns it changes the law theorem. In the meantime, the nas related to this discussion is very limited, the exploration on ulamaâs thoughts is badly needed, particularly those that closely connected to the discussion of maslahat. This way, it can be proven that Islamic syariat is in line and adaptable to the rapid changes of any condition and from time to time even since Al-Qurâan bestowed the human being until the end of time. This research is a library research. The exploration is conducted through analyzing descriptively. The researcher describes the thoughts of proposed by ulamas thoughts their mazhab and then compare them critically before finally composing concluding remarks. The result of this research shows that maslahat as the law theorem of Islam is accepted by all mazhab such as Hanafi, Maliki, Syafii and Hambali.. Furthermore, the use of maslahat is various based on the knowledge background. The way people see maslahat may be influenced by certain given condition and situation.Â Keywords: Islamic law, maslahat.